Między wieloznacznością a uprecyzyjnieniem pojęcia „dyskurs”. Miejsce tekstu w germanistycznych ujęciach dyskursu - Bilut-Homplewicz, Zofia (Stylistyka, 2019)
Despite the ambiguity of the term discourse in German studies on discourse, a tendency is visible to specify the term for the purposes of particular research studies. These issues are addressed in the opening sections of the article. The article also discusses the relation between text and discourse, and reaches the conclusion stating that discourse linguistics is more than merely an extension of text linguistics, as both phenomena, i.e., text and discourse display a difference in quality. A question is also raised about the place of text in various trends of research on discourse. Particular schools/research groups show diversity in terms of theoretical conceptions, research methods, as well as in relation to the reception of Foucault’s ideas. Texts are in them undoubtedly an element of continuing discourse in the sense of corpus, in discourse analysis itself, however, researchers frequently focus only on selected linguistic aspects, rarely relying on text linguistics tools. The closing sections present a few suggestions within text-oriented discourse linguistics, which is understood here as a trend of the evolutionary character.